Structural Elements Required for Association of the Saccharomyces cerevisiae Telomerase RNA with the Est2 Reverse Transcriptase - Chappell, Andrew S. (American Society for Microbiology, 2004)
Telomere synthesis in most organisms depends on the action of the telomerase enzyme, which contains an RNA subunit that is stably associated with the reverse transcriptase subunit as well as additional telomerase proteins. In the budding yeast Saccharomyces cerevisiae, several structural domains that are responsible for mediating protein interactions with the telomerase RNA TLC1 have been identified. We report here the identification and characterization of a TLC1 stem-loop that is required for its interaction with the Est2 reverse transcriptase protein. This hairpin, which does not contain any bulges in the duplex stem that commonly mediate protein-RNA interaction, appears to be a part of a larger structure, as nucleotides immediately to either side of this stem-loop contribute to the interaction of TLC1 with the Est2 protein. Surprisingly, replacement of a 95-nucleotide region of the yeast telomerase RNA that is required for Est2 interaction with a 39-nucleotide pseudoknot from a distantly related telomerase RNA results in a functional telomerase enzyme. These findings suggest that the ability of the budding yeast reverse transcriptase to associate with the telomerase RNA depends on a highly structured region rather than specific sequence elements.